Coexistence in a one-dimensional cyclic dominance process - Winkler, Anton A.; Reichenbach, Tobias; Frey, Erwin (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2010)
Cyclic (rock-paper-scissors-type) population models serve to mimic complex species interactions. Focusing on a paradigmatic three-species model with mutations in one dimension, we observe an interplay between equilibrium and nonequilibrium processes in the stationary state. We exploit these insights to obtain asymptotically exact descriptions of the emerging reactive steady state in the regimes of high and low mutation rates. The results are compared to stochastic lattice simulations. Our methods and findings are potentially relevant for the spatiotemporal evolution of other nonequilibrium stochastic processes. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2021-02-25